Dynamic emergency image as a mechanism of efficiency enhancement of its elimination - Bogomaz, Ольга Владимировна (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2016)
Сharacteristics of compiling and functioning of an emergency image in rescuers' consciousness as a peculiar image of the dynamic object are considered in the article. The datum points method is described, and the possibility of using is considered in system for training of rescuers.